Comparative analysis of the leprosy detection rate regarding its clinical spectrum through PCR using the 16S rRNA gene: a scientometrics and meta-analysis - Silva, Marcos Jessé Abrahão; Brasil, Thiago Pinto; Silva, Caroliny Soares; Frota, Cristiane Cunha; Sardinha, Daniele Melo; Figueira, Luiza Raquel Tapajós; Neves, Keitty Anne Silva; dos Santos, Everaldina Cordeiro; Lima, Karla Valéria Batista; Ghisi, Nédia de Castilhos; Lima, Luana Nepomuceno Gondim Costa (Frontiers in Microbiology, 2024)
Leprosy is a chronic and disabling infectious disease caused by Mycobacterium leprae. It has a wide clinical spectrum and is operationally classified into paucibacillary (PB) and multibacillary (MB) cases. Evidence shows that the 16S rRNA gene can be used in Polymerase Chain Reaction (PCR) for complementary detection with high sensitivity and specificity. However, there is no literature convention on its diagnostic correspondence regarding the particular operational classification of the disease. This study aimed to correlate, through a meta-analysis, the detection rate of leprosy between the PCR method with the 16S rRNA gene in the clinical forms PB and MB concerning confirmed cases. This is a systematic review and meta-analysis study conducted according to the PRISMA 2020 guidelines, using the search descriptors with “AND”: “Leprosy”; “Polymerase Chain Reaction”; “16S rRNA” in the PUBMED, SciELO, LILACS, and Science Direct databases. The search was limited to original observational articles in Portuguese, English, or Spanish, with no defined time frame. The methodological quality assessment of the selected articles was performed using the JBI checklists. A scientometric approach to the article used the VOS Viewer and Scimago Graphica software. The meta-analysis was conducted using Comprehensive Meta-Analyses software, under Pearson's Correlation effect test and fixed effect model and subgroup analysis concerning the type of sample analyzed. The study was significant from the perspective of the paucibacillary group (Clinical biopsy: -0.45 [95% CI= -0.63 – -0.22], p<0.001/ Slit smear skin: -0.52 [95% CI= -0.65 – -0.36], p<0.001 / Overall: -0.50 [95% CI= -0.61 – -0.37], p<0.001). The PCR diagnostic method for the 16S rRNA gene of M. leprae has low viability and diagnostic sensitivity in both clinical biopsy samples and leprosy skin smears. This implies little validation of it as a PCR target gene for diagnosing the disease, highlighting limitations in the actual technique.